Analysis the Influence of Job Embeddednes and Work Engagement on Improving Employee Performance in Rsud Haji of South Sulawesi Province in 2020 (Medico Legal Update, 2020)
Performance is the result of quality and quantity of work achieved by employees in carrying out their dutiesin accordance with the responsibilities given to them. The role of reliable and professional employees is veryhelpful in improving organizational performance. The quality of employees who are still far from adequatewill certainly affect the achievements. This study aims to analyze the Influence of Job Embeddednes andWork Engagement on Improving Employee Performance in RSUD Haji of South Sulawesi Province in 2020.The type of research conducted is quantitative research using observational studies with cross sectionalstudy design. The sample in this study were employees who worked at RSUD Haji with 240 respondents.The results showed there was an influence of job embeddedness on employee performance (p = 0,000), therewas an influence of job embeddedness on work engagement (p = 0,000), there was an influence of workengagement on performance (p = 0,000), and there was no influence of job embeddedness on employeeperformance through work engagement (coefficient = 0.146). It is recommended to the hospital managementto increase the embeddedness and engagement of employees, where employees can feel the compatibility ofthe work and improve the formal or informal relationship between an employee and the hospital environmentso that the impact on improving the quality and performance of the hospital.